Improved jet lag recovery is associated with a weaker molecular biological clock response around the time of expected activity onset - Boutrin, Marie-Claire; Richardson, Melissa E. S.; Oriola, Feyikemi; Bolo, Samira (Frontiers in Behavioral Neuroscience, 2025)
IntroductionProperly timed environmental light input to the suprachiasmatic nucleus (SCN) in the brain is crucial in maintaining the 24-hour biological rhythm (circadian rhythm). However, light exposure at the wrong time of the day-night cycle is disruptive to circadian-regulated behaviors such as the sleep-wake cycle and memory. While factors such as jet lag, variations in day length, and light at night are known disruptors to the timing of activity onset following rest, the molecular consequence of the intersection of multiple disruptions is less understood.MethodsHere, we expose mice to a jet lag paradigm under two light-dark (LD) conditions (12:12 LD and 8:16 LD) coupled with additional light exposure at night during the recovery period (known as negative masking), previously demonstrated to improve jet lag-related memory loss in mice.ResultsOur results show that jet lag exposure in both LD cycles (to a greater extent in 8:16 LD) increased the fold-change of circadian gene expression in the SCN relative to the dark onset. The further addition of light during the jet lag recovery period reduced typical changes in circadian gene expression in the SCN to minimal levels under both LD cycles.DiscussionThis study uncovers a novel explanation for the impact of multiple disruptive light exposures on gene expression of the molecular SCN clock in the brain.